Complexities in the simple optimization of wood production and carbon sinks - Samuli Korhonen; Olli Tahvonen (Helsinki Graduate School of Economics, 2023)
To resolve several open issues in the forestry and carbon literature, we apply an analytically solvable stand-level model for optimizing the values of wood production and carbon sinks. Nonmonotonic stand volume development is shown to lead to locally optimal finite and infinite rotations. With infinite rotation, forests are most valuable as a carbon storage, and this outcome is shown to depend on discount rate and, in specific situations, on initial stand age. A rotation maximizing the pure value of carbon sinks is proved to lengthen with discount rate. In contrast to existing understanding, zero discounting does not render carbon sink enhancement as superfluous; instead, maximizing the average carbon stock in standing forests and decaying wood products is optimal. This combined with wood production implies that optimal rotation is, excluding accidental parameter values, discontinuous at a zero discount rate. These results have far-reaching implications in the comparisons of carbon sink studies. Including carbon into the optimal rotation model changes the rationale of stand value and its development over the rotation.
Keywords: Q23; Q54; 330; forest carbon sink; optimal rotation; discounting; carbon neutrality; climate and forest policy